The Politics of Giving in the Viceroyalty of Rio de la Plata : Donors, Lenders, Subjects, and Citizens - Grieco, Viviana L., 1969- (Book collections on Project MUSE., 2014)
This book examines an eighteenth century Spanish state finance based on voluntary donations rather than taxes. The author analyzes the "gifts" (donativos) that residents of colonial Argentina gave to the Spanish Crown and the city council of Buenos Aires.